Co-design of the scaling strategy Mechanized DSR and tailored agronomy in Cambodia - Flor, Rica Joy (International Rice Research Institute, 2022)
The presentation discussed the co-design of the scaling strategy of mechanized direct seeded rice and tailored agronomy in Cambodia. Presented at the Excellence in Agronomy Meeting in Sofitel Phnom Penh, Cambodia on 30 November 2022.